Perceiving landscape: designing for the contemplation of material culture through time - Myers, Amber (School of Architecture, Planning and Geomatics, 2021)
Near the Point at Mossel Bay on the Cape south coast is a series of sea cliff caves that contain the earliest known evidence of modern human material culture: a record of complex tool use, collection of marine resources for food and use of natural pigments for symbolling practices. This is revealed by the archaeological excavation of 'midden' deposits - piles of refuse usually situated in the back of cave dwellings left by their ancient occupants. This evidence reveals that modern humans have lived on the Cape south coast for at least 167 000 years, a time spanning global glacial and interglacial periods with associated sea level retreat and rise. During glacial phases of sea level retreat - the norm during much of human evolution - a broad continental shelf was exposed on the Cape south coast, creating a coastal plain up to 90km from the present shoreline. This now-submerged landscape, uniquely temperate, well-watered and productive during harsh glacial phases, provided sanctuary for human and other life. It is thought that this landscape was critical in establishing the course of modern human cognition. A geological study of this coastal landscape reveals its sedimentary nature, the result of repeated processes of erosion and deposition. Notions of erosion and deposition are echoed by human interaction with materials through time. Humans extract material resources from the landscape, transform them, and then deposit them, changing the landscape. The urban landscape of modern Mossel Bay consists of a palimpsest of material traces deposited through time, forming an aggregate of layers of human history. As we enter the uncertain future of climate change and sea level rise, we must be conscious of what we deposit on the landscape. This forces a re-evaluation of our material use as designers and as a society. These considerations animated the choice of the Point in Mossel Bay as the location of a landscape design intervention - a space at the intersection of sea, shoreline, cliff, quarry, cave and plain, that has developed haphazardly in the modern era. The design, which envisions a modern 'midden,' a mound of demolition waste deposited over the existing site to form the new public landscape, impels a contemplation of the layers of material that we leave behind over time, and how this defines us to future generations. A design language derived from the language of geology (erosion, deposition) and archaeology (trace, excavation) informs the design and its experience. The fill material for the midden/mound is from two sources: the zones of settlement that will be forced to retreat from the shoreline due to sea level rise anticipated in the next 50 years, and the existing materials on site that are repurposed in the design of the new landscape. The design allows people to perceive and reflect on the layers of materiality that make up the human landscape, and on the possibilities of the thoughtful use of materials that will give way to the landscapes of the future.